1987
DOI: 10.1901/jeab.1987.47-299
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Temporal Discrimination in Pigeons: A Comparison of Two Procedures

Abstract: A within-subjects comparison was made of pigeons' performance on two temporal discrimination procedures that were signaled by differently colored keylight samples. During stimulus trials, a peck on the key displaying a slanted line was reinforced following short keylight samples, and a peck on the key displaying a horizontal line was reinforced following long keylight samples, regardless of the location of the stimuli on those two choice keys. During position trials, a peck on the left key was reinforced follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…These include manipulations of the nature of the discriminative response (Chatlosh & Wasserman, 1987); the psychophysical method (Fetterman, 1995); choice versus successive DMTS (Grant & Spetch, 199 I;; III (Spetch & Rusak, 1989; the mapping of samples to comparison stimuli When the light duration was tested, there was no difference in accuracy between baseline and same trials (F < I). Accuracy was significantly lower on different trials than on baseline trials, however [F(l,6) …”
Section: Discussionmentioning
confidence: 99%
“…These include manipulations of the nature of the discriminative response (Chatlosh & Wasserman, 1987); the psychophysical method (Fetterman, 1995); choice versus successive DMTS (Grant & Spetch, 199 I;; III (Spetch & Rusak, 1989; the mapping of samples to comparison stimuli When the light duration was tested, there was no difference in accuracy between baseline and same trials (F < I). Accuracy was significantly lower on different trials than on baseline trials, however [F(l,6) …”
Section: Discussionmentioning
confidence: 99%
“…Graham et al (1994) offered an alternative explanation for the lesion-induced shift of the bisection point. They noted that rats performing the interval bisection task often assume a position close to lever A (the lever appropriate to the short stimulus) at the start of trial, and then migrate across the chamber towards lever B (the lever appropriate to the long stimulus) as the period of stimulus presentation progresses (see also Chatlosh and Wasserman, 1987). Could destruction of the 5-HTergic pathways have facilitated the rats' movement across the chamber from lever A to lever B?…”
Section: Behavioural Definitions Of Impulsivenessmentioning
confidence: 99%
“…Although such differential sample behavior was not explicitly required or reinforced in the present experiment, it may have been maintained by the reinforcers obtained for choosing the correct comparison (i.e., by adventitious reinforcement; see e.g., Blough, 1959), especially given the close temporal proximity between the sample and comparison presentations. Indeed, some studies have shown that subjects engage in differential sample behavior in DMTS tasks with longer intervals (e.g., 5 s) between sample offset and comparison onset than that arranged here, even when such behavior is not required (e.g., Blough, 1959;Chatlosh & Wasserman, 1987;Chudasama & Muir, 1997;Hunter, 1913). Thus, whereas comparison-key choice was controlled by the stimulus that the pigeons attended to in previous dividedattention experiments, comparison-key choice probably did not reflect attention allocation accurately in the present experiment because such choice was strongly controlled by the location of the last-pecked sample key.…”
Section: Discussionmentioning
confidence: 77%